Policy and theoretical implications of the zero-subsidy bids in the German offshore wind tenders - Greve, T.; Rocha, M. (Energy Journal, 2020)
The German offshore wind tender, launched in April 2017, resulted in three out of the four winning projects being delivered with zero subsidies, relying only on the wholesale price. This result has been regarded as a turning point for the industry. This paper analyses the 2017/18 German offshore wind tenders and the bidding strategies of the winning developers. We then propose a re-design of the tenders with the aim of achieving optimality/zero-subsidies and efficiency - two key properties in mechanism design. The paper contributes to the discussion on how to design offshore wind tenders with both a policy and theoretical perspective. This is of particular relevance given the rapid expansion of this type of investment in Europe and the use of auctions to select developers.